Associations of Substance Use Problems with Intimate Partner Violence for At-Risk Men in Long-Term Relationships - Feingold, Alan (2008)
Associations of men’s substance use problems–defined as meeting at least one criterion of dependence on each of a number of substances by the mid-20s–and their perpetration of intimate partner violence (IPV) were examined in an at-risk community sample of 150 men in long-term relationships from late adolescence to the late 20s. Men who had a problem with substances other than sedatives (especially cannabis and hallucinogens) committed more IPV than did men without such problems. Most of the men who had a problem with marijuana also had an alcohol problem, explaining why alcohol was found to have only an indirect association with IPV. The failure of previous alcohol-use studies to control for co-occurrence of alcohol and marijuana problems may explain the discrepancy with conclusions from past research that alcohol problems contribute directly to the perpetration of IPV.